Draft Annual Plan (2004-05) Proposals (Write-Up) Volume-I Government of Manipur - Planning Commission (Planning Commission, 2004)
Manipur is one of the border states in the north-eastern part of the country having an international boundary of about 352 kms. long stretch of land with Myanmar on the east. It is bounded by Nagaland on the north, Assam on the west and Mizoram on the south. It has a total area of 22327 sq. kms of which nine-tenth consists of hills and only one-tenth comprises the valley. Manipur is divided into 9 districts namely, Imphal West, Imphal East, Thoubal, Bishnupur, Churachandpur, Senapati, Chandel, Tamenglong and Ukhrul.
Government of Manipur Planning Department